(untitled) (Scientific journal of the Fergana State University, 2023)
Uzbekistan is constantly expanding cooperation in the field of education, including joint training with foreign educational institutions. Interest in the Russian language in our country is growing: more and more Uzbek youth are striving to learn it. At present, the global goal of mastering the Russian language is the opportunity to participate in the dialogue of cultures. At the same time, it is not just about knowing the language, but about the ability to use it in real communication, that is, about practical knowledge of the language. In this regard, the following aspects are considered in the article features of teaching Russian language to students of technical universities, organization of teaching the Russian language in a functional context; basic principles of teaching Russian as a foreign language; the main methodological approaches to teaching students in the context of the form of organization of their knowledge; increasing the intellectual and general cultural level of students’ knowledge in the study of the Russian language; the possibility of improving the form of organization of knowledge in teaching students.